Environmental DNA detection of an invasive ant species (Linepithema humile) from soil samples - Tetsu Yasashimoto (Nature Portfolio, 2021)
Abstract Alien ant species (Formicidae, Hymenoptera) cause serious damage worldwide. Early detection of invasion and rapid management are significant for controlling these species. However, these attempts are sometimes hindered by the need for direct detection techniques, such as capture, visual observation, or morphological identification. In this study, we demonstrated that environmental DNA (eDNA) analysis can be used as a monitoring tool for alien ants using Linepithema humile (Argentine ant), one of the most invasive ants, as a model species. We designed a new real-time PCR assay specific to L. humile and successfully detected eDNA from the surface soil. The reliability of eDNA analysis was substantiated by comparing eDNA detection results with traditional survey results. Additionally, we examined the relationship between eDNA concentration and distance from nests and trails. Our results support the effectiveness of eDNA for alien ant monitoring and suggest that this new method could improve our ability to detect invasive ant species.